Galectin-1-Dependent Mitochondria Apoptosis Plays an Essential Role in the Potential Protein Targets of DBDCT-Induced Hepatotoxicity as Revealed by Quantitative Proteomic Analyses - Jiayu Song; Yuan Ren; Lihua Liu; Yixin Wang; Chuandao Shi; Xiaoqing Ji; Yunlan Li; Qingshan Li (Bioinorganic Chemistry and Applications)
Di-n-butyl-di-(4-chlorobenzohydroxamato) tin(IV) (DBDCT), a new patent agent, exhibited strong antitumor activity. In some cases, its activity was close to or even higher than cisplatin, a first-line clinical metallic agent. Similar to platinum compounds, it also showed toxicity. However, the effective targets and mechanisms for specific toxicity and biological activity are still unclear. In this study, proteomic analysis revealed that 146 proteins (98 upregulated and 48 downregulated) were differentially identified by label-free LC-MS/MS after DBDCT treatment. Meanwhile, network analysis of these differential proteins suggested that protein Galectin-1 (Gal-1) could regulate the apoptosis process (15 related proteins), which played an essential role in the potential targets of DBDCT-induced hepatotoxicity. Furthermore, it was demonstrated that DBDCT might promote ROS production, activate NF-κB p65, inhibit Ras and p-ERK1/2 expressions, increase the level of Gal-1, subsequently upregulate the expressions of Bax, p53, Fas, and FasL, and downregulate the expression of Bcl-2. As a result of these modulations, caspase cascades were finally activated, which executed apoptosis in HL7702 liver cells. Correspondingly, NAC (inhibitor of ROS), PDTC (inhibitor of NF-κB), EGF (ERK1/2 activator), and OTX008 (inhibitor of Gal-1) were found to reverse and abolish the DBDCT-associated cytotoxicity partially. In conclusion, Gal-1 might be the potential target for toxicity and biological activity. Moreover, the present study will lay the groundwork for future research about di-n-butyl-di-(4-chlorobenzohydroxamato) tin structure optimization and developing it into a new potential anticancer agent.